Macro-Anatomical Investigations on Neurocranium and Splanchnocranium in Dalmatian pelican (Pelecanus crispus) - İlgün, Ramazan; Özkan, Zait Ender; Akbulut, Yalçın (Van Yüzüncü Yıl Üniversitesi, 2017)
In this study, it was aimed to investigate the neurocranial and splanchnocranial bones of Dalmatian pelicans located in Pelecanidae family. The cranium bones three adult female dalmatian pelicans were macerated. It was observed that the neurocranium consists of the occipital, sphenoid, parietal, frontal and squamosal bones. The splanchnocranium consisted of the ethmoidal, lacrimal, nasal, intermaxilla, maxilla, zygomatic, palatine, ptergoid, vomer, quadrate and mandible bones. It was determined that the interparietal bone was absent. The intermaxillar bone formed long and sharp beak. The occipital condyles were spherical located to below foramen magnum. In conclusion, the bones forming the neurocranium and splanchnocranium in Dalmatian pelicans were investigated and significant differences with respect to the other avians were determined.

Bu araştırmada Pelecanidae familyasında yer alan tepeli pelikanın neurocranium ve splanchnocranium kemiklerinin incelenmesi amaçlandı. Üç adet yetişkin dişi tepeli pelikan kafatası kemikleri masere edildi. Neurocranium; os occipitale, os sphenoidale, ossa parietalia, ossa frontalia ve os squamosum’dan. Splanchnocranium; os ethmoidale, os lacrimale, os nasale, os intermaxillare, os maxillare, os zygomaticum, os palatinum, os pterygoideum, os vomer, os quadratum, os mandibulae’dan oluşmaktaydı. Os interparietale’nin bulunmadığı tespit edildi. Os intermaxillare oldukça keskin ve uzun olarak gagayı oluşturmaktaydı. Condylus occipitalis küre biçiminde foramen magnum’un altında yer almaktaydı. Sonuç olarak; tepeli pelikanların neurocranium ve splanchnocranium’unu oluşturan kemikler makroanatomik olarak incelenerek diğer kanatlılarla arasındaki önemli farklılıklar ortaya konuldu.
Tepeli pelikanların (Pelecanus crispus) Neurocranium ve Splanchnocranium kemikleri Üzerinde Makro-Anatomik İncelemeler